P-747 Prevalence of Caesarean scar defect (CSD) and clinical impact on reproductive outcomes in patients undergoing in vitro fertilization (IVF). (30th June 2022) - Mensi, L; Riccaboni, A; Alagna, F; Benaglia, L; Filippi, F; Reschini, M; Somigliana, E
Abstract: Study question: Can sonohysterography-detected CSD have a deleterious effect on reproductive outcomes in women with secondary infertility undergoing IVF? Summary answer: A 68% prevalence of CSD has been estimated in the study population. CSD significantly reduces the ongoing pregnancy rates in women undergoing IVF cycles. What is known already: here is limited and conflicting evidence about the relation between Caesarean section, CSD and IVF treatment outcomes. Notably, most of the previous studies did not investigate the presence of CSD in infertile women with a history of Caesarian delivery. Furthermore, even if considered, the diagnosis of CSD is commonly based on transvaginal ultrasound assessment. Given the lower sensitivity of this method compared to saline infusion sonohysterography, an underestimation of the real effect is plausible. Study design, size, duration: Retrospective cohort study of 122 women with a history of Caesarean delivery and an indication to IVF for secondary infertility referred to an Italian public assisted reproductive centre between 1 January 2016 and 30 April 2021. Participants/materials, setting, methods: Women aged 18-43 with secondary infertility and a history of Caesarean delivery, tested for CSD with a saline infusion sonohysterography were included. Women with congenital uterine anomalies, intra-cavitary uterine pathologies, adenomyosis or previous myomectomy were excluded. CSD was defined as an anechoic indentation on the cesarean scar at the midsagittal plane, with a depth ≥ 2 mm. Main results and the role of chance: Among the 122 women included, 83 (68%) were diagnosed with CSD by saline infusion sonohysterography. One hundred and fourteen patients underwent at least one IVF cycle: 76 (case group) had a CSD, 38 (control group) had a normal Caesarean scar. Groups were similar in patients and treatment characteristics. Clinical pregnancy rate was 43% in the CSD group and 71% in the control group (odds ratio [OR] 0.31; 95% confidence interval [CI], 0.14-0.72; p = .006). Ongoing pregnancy rates were 33% and 58%, respectively (OR, 0.34; 95% CI, 0.15-0.76; p = .015). Similar results were obtained after adjusting for potential confounders on the regression analysis. Ectopic pregnancy and miscarriage rate along with obstetric and neonatal complications were similar in both groups. In a subgroup-analysis comparing women with CSD who achieved pregnancy and those who did not, pregnant patients had a greater residual myometrial thickness compared to those who did not get pregnant, even if this finding did not reach statistical significance (5.3 mm versus 4.4 mm, p .07). Limitations, reasons for caution: Retrospective nature of the study does not permit to infer a causal association between CSD and the reduced chance of pregnancy. Our results are representative of an infertile population but generalization needs further investigation. The sample size was too small to reveal the potential effect on obstetric and neonatal outcomes. Wider implications of the findings: In infertile patients with a previous Caesarean section, the presence of CSD is more common than previously thought. The presence of CSD might significantly reduce the IVF success rate. This finding is important in relation to the rising of Caesarean section rates and the possible application of CSD surgical repair. Trial registration number: not applicable